MODERN EDUCATIONAL ACTIVITY AIMED AT TRAINING HIGHLY QUALIFIED SPECIALISTS – DOCTORS AND PHARMACISTS, WHO ARE ABLE TO SOLVE PROFESSIONAL TASKS AND TAKE RESPONSIBILITY FOR THEIR SOLUTION IN THE SYSTEM OF LEGAL RELATIONS "DOCTOR-PATIENT-PHARMACIST" - Haiduchok Ігор; Gumenyuk Ольга (Actual Problems of Medicine and Pharmacy, 2024)
WHO indicates that at least 140 countries recognize the right of citizens to health in their constitutions. Every citizen or patient deserves access to quality, timely and appropriate health care services without discrimination or financial hardship. The modern educational activity of the Lviv Medical University Medical University for the training of highly qualified specialists - doctors and pharmacists - was considered. It has been proven that graduates are able to solve professional tasks and take responsibility for solving them in the system of legal relations "doctor-patient-pharmacist". The improvement of the system of legal relations "doctor-patient-pharmacist" during the medical reform and the implementation of the Action Plan of the Cabinet of Ministers of Ukraine for self-realization, employment and active, responsible citizenship in accordance with the European educational space is analyzed. The priorities in the activities of the rectorate, deans, heads of departments, professors and teachers and teaching staff of the Lviv Medical University Medical University are given. The teaching of first aid in the conditions of hostilities, master classes in tactical medicine for students is outlined. The scientific results of the University's work are presented. Attention is focused on the organization and holding on November 14-15, 2024 of the XXI International multidisciplinary scientific and practical conference "Medical and pharmaceutical law of Ukraine: organization and economy of pharmaceutical and medical affairs, circulation of drugs, technology, safety, efficiency, quality control, general, judicial, evidence-based and clinical pharmacy and medicine, pharmacotherapy of health disorders" (Registration number of the Provider – No. 2102, in accordance with the Regulation on the system of continuous professional development of health care workers approved by the Resolution of the Cabinet of Ministers of Ukraine dated July 14, 2021 No. 725).